(untitled) (Indian Journal of Child Health, 2019)
Background: Institutional delivery and in utero transport of the newborn is the safest method of neonatal transport. However, neonatal illnesses cannot always be predicted, resulting in the continued need of transfer of these babies after delivery. Objective: The objective of the study was to analyze the adverse events related to transfer of neonates to a tertiary center of Central India, the impact of the epidemiological factors, and the role of temperature, oxygenation, perfusion, and blood sugar (TOPS) scoring in predicting mortality in transferred neonates. Materials and Methods: This observational study was conducted at the special care newborn unit of a tertiary teaching hospital of Indore. A total of 217 transported neonates were included in the study. The TOPS scoring for each neonate was done at admission and the parameters of the TOPS score were correlated with the outcome. Results: The common indications for referral were respiratory distress in 103 (47.4%), prematurity/low birth weight care in 31 (14.2%), sepsis in 27 (12.4%), seizures in 21 (9.6%), and neonatal hyperbilirubinemia in 16 (7.3%) cases. At the time of admission, 25.4% of neonates had normal temperature, while 31.8% had temperature between 96.8 and 97.6°F, and 42.9% had hypothermia (89.6–96.6°F). Almost 5.1% of admitted neonates were hypoglycemic (<45 mg/dl) and rest 94.9% were normoglycemic (>45 mg/dl). Hypoxemia (oxygen saturation <90%) was seen in 51.6% of neonates and 16.1% of neonates had prolonged capillary refill time at admission. A higher TOPS score of 3 and 4 was correlated with higher incidence of mortality. Conclusion: TOPS score is a useful and easy to use method to assess the physiological status and helps in prediction of mortality in neonatal transport.